Characteristics of Bilayer Molybdenum Films Deposited Using RF Sputtering for Back Contact of Thin Film Solar Cells - Sea-Fue Wang; Hsiao-Ching Yang; Chien-Fong Liu; Huy-Yun Y. Bor (Advances in Materials Science and Engineering)
Mo films prepared under a single deposition condition seldom simultaneously obtain a low resistivity and a good adhesion necessary for use in solar cells. In order to surmount the obstacle, bilayer Mo films using DC sputtering at a higher working pressure and a lower working pressure have been attempted as reported in the literature. In this study, RF sputtering with different powers in conjunction with different working pressures was explored to prepare bilayer Mo film. The first bottom layer was grown at a RF sputtering power of 30 W and a working pressure of 12 mTorr, and the second top layer was deposited at 100 W and 4.5 mTorr. The films revealed a columnar growth with a preferred orientation along the (110) plane. The bilayer Mo films reported an electrical resistivity of 6.35 × 10−5 Ω-cm and passed the Scotch tape test for adhesion to the soda-lime glass substrate, thereby qualifying the bilayer Mo films for use as back metal contacts for CIGS substrates.